A widely applicable method to stabilize nanoparticles comprising oxygen-rich functional groups - Distaso, Monica; Lautenbach, Vanessa; Uttinger, Maximilian; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Peukert, Wolfgang (Powder Technology, 2022)
Colloidal stability of nanoparticle suspensions is fundamental to apply nanomaterials in functional devices and to develop new methodologies in nanoscience. Herein, a versatile method is described to disperse and stabilize various solids with technological applications in pharmaceutical industry, batteries and fuel cells, dye sensitized solar cells, pigments and coatings. The method is based on the use of Zr(IV) hydroxo-complexes that interact with carboxylic- and hydroxo- functional groups at the solid-liquid interfaces of active pharmaceutical ingredients (API), carbon black (CB) and Pt-CB, metal oxide and metal oxy-hydroxide nanoparticles. The colloidal stability is assessed via sedimentation analysis, electrophoretic measurements, ultraviolet-visible spectroscopy (UV–Vis), attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) and isothermal titration calorimetry (ITC). The effect of the anion and pH are studied in depth. Finally, the current work enables liquid phase length and diameter characterization of rod-like goethite (α-FeOOH) particles without relying on tedius counting the particles from electron micrographs.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Functional devices; Nanoparticles; Nanoparticulate inks; Stability; Surface